2020
DOI: 10.3390/app10103359
|View full text |Cite
|
Sign up to set email alerts
|

How Deeply to Fine-Tune a Convolutional Neural Network: A Case Study Using a Histopathology Dataset

Abstract: Accurate classification of medical images is of great importance for correct disease diagnosis. The automation of medical image classification is of great necessity because it can provide a second opinion or even a better classification in case of a shortage of experienced medical staff. Convolutional neural networks (CNN) were introduced to improve the image classification domain by eliminating the need to manually select which features to use to classify images. Training CNN from scratch requires very large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…As pointed out by [ 19 , 41 ], fine-tuning the CNN architectures will yield better results and converge faster than training a CNN from scratch. In this paper, we fine-tuned all CNN layers using the ImageNet dataset.…”
Section: Resultsmentioning
confidence: 99%
“…As pointed out by [ 19 , 41 ], fine-tuning the CNN architectures will yield better results and converge faster than training a CNN from scratch. In this paper, we fine-tuned all CNN layers using the ImageNet dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Choosing the most suitable layer to begin fine-tuning from requires extensive testing. Studies such as [ 12 ] have investigated which block to tune from such that results are optimal. The authors [ 12 ] concluded that fine-tuning the top layers of a network is much more beneficial than the entire network.…”
Section: Methods and Techniquesmentioning
confidence: 99%
“…In general, the shortage of available medical experts [ 12 ], the time-consuming quest to reach a final decision on a diagnosis, and the issue of interobserver variability justify the need for a system that can automatically and accurately classify breast cancer histopathology images. Previous approaches to this problem have been relatively successful considering the available data and return adequate classification accuracies but tend to be computationally expensive.…”
Section: Introductionmentioning
confidence: 99%
“…A u‐net consisting of a block depth of five layers and 113,306 parameters was trained on these image patches in an autoencoding fashion to produce a baseline model, a process shown to learn features associated with tissue presentation [ 16 ]. This base model is subsequently fine‐tuned in a supervised fashion to segment the structure of interest, a common approach to help reduce annotated data requirements [ 17 ]. Next, the user viewed all patches processed by this model in a uniform manifold approximation and projection (UMAP [ 18 ]) plot (Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%